1989
DOI: 10.1111/j.1399-0004.1989.tb02958.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of de novo trisomy 12p syndrome

Abstract: A case of pure 12p trisomy was discovered in a 14‐year‐old boy during a cytogenetic survey of Egyptian students attending a school for mentally retarded children. The patient had a normal birth weight but later showed developmental delay. Clinical examination at 14 years of age revealed a high bulging forehead, broad and flat nasal bridge, large mouth with everted lower lip, folded upper ear helix with protuberant antihelix, pectus excavatum, undescended testes, flat feet, generalized hypotonia and moderate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In addition to the new case reported here, we identified 21 reports describing a total of 26 individuals with 12p duplications of varying sizes (15 cases were partial 12p duplication, one case had partial 12p triplication and 10 cases had duplication of the entire 12p) [Armendares et al, 1975; Biederman et al, 1977; Tenconi et al, 1977; Hansteen et al, 1978; Parslow et al, 1979; Dallapiccola et al, 1980; Stengel‐Rutkowski et al, 1981; Ray et al, 1985; Rivera et al, 1987; Tayel et al, 1989; Pfeiffer et al, 1992; Zelante et al, 1994; Allen et al, 1996; Rauch et al, 1996; Back et al, 1997; Rivera et al, 1999; Tekin et al, 2001; Zumkeller et al, 2004; De Gregori et al, 2005; Tsai et al, 2005; Eckel et al, 2006; Liang et al, 2006; Cetin et al, 2011]. Ages of the patients described in the previously published case reports ranged from birth to 34 years.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the new case reported here, we identified 21 reports describing a total of 26 individuals with 12p duplications of varying sizes (15 cases were partial 12p duplication, one case had partial 12p triplication and 10 cases had duplication of the entire 12p) [Armendares et al, 1975; Biederman et al, 1977; Tenconi et al, 1977; Hansteen et al, 1978; Parslow et al, 1979; Dallapiccola et al, 1980; Stengel‐Rutkowski et al, 1981; Ray et al, 1985; Rivera et al, 1987; Tayel et al, 1989; Pfeiffer et al, 1992; Zelante et al, 1994; Allen et al, 1996; Rauch et al, 1996; Back et al, 1997; Rivera et al, 1999; Tekin et al, 2001; Zumkeller et al, 2004; De Gregori et al, 2005; Tsai et al, 2005; Eckel et al, 2006; Liang et al, 2006; Cetin et al, 2011]. Ages of the patients described in the previously published case reports ranged from birth to 34 years.…”
Section: Resultsmentioning
confidence: 99%
“…For cases of isolated complete trisomy 12p (involving bands p11.22 to pter) with no other chromosomal abnormalities, there were only five de novo cases with confirmed normal parental karyotypes [Kondo et al, ; Ray et al, ; Guerrini et al, ; Karki and Walters, ; Rauch et al, ]. Two additional cases involved breakpoints in the 12p12‐>12pter region [Tayel et al, ; Allen et al, ]. The actual number might be even fewer as some of the earlier reports were based on conventional karyotype analysis with no FISH or aCGH results, and the duplication might not involve the entire short arm.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, partial duplication of the short arm of chromosome 12(pter-+p13.2 rsp.pl3.1) has been described in three patients (Leana-Cox et al 1993, Rauch et al 1996, cases 2 and 3), whde duplication of 12(pter-+p12) has been reported in nine cases from eight families (Uchida & Lin 1973, Tenconi et al 1977, Hansteen et al 1978, nos. 1 and 3, Serville et al 1978, Dallapiccola et al 1980, Kubryk et al 1980, Hernandes Encinas et al 1983, Tayel et al 1989. Except for the cases of Uchida &Lin 1973, Serville et al 1978, and De nova dup(lt)(pter+pl2.1) Kubryk et al 1980, all of them carry a pure duplication, like the patient described here.…”
Section: Discussionmentioning
confidence: 51%
“…Only 12 cases were de novo events, two of them caused by isochromosome formation of the entire short arm (Rivera et al 1987, Marques-de Faria et al 1989, one by an additional del( 12)(qll) chromosome as a mosaic with a normal cell line (Kondo et al 1979), four by translocation of 12p onto the short arm of an acrocentric or an undefined chromosome (Dallapiccola et al 1980, Ray et al 1985, Guerrini et al 1990, Allen et al 1996. three by direct tandem duplication of 12pter-p12.1 rsp.pl3.1, the second as a mosaic (Tayel et al 1989, Leana-Cox et al 1993, Rauch et al 1996, and a further two by inverted tandem duplication of 12p13.3+p11.2 rsp.pI3.2, the latter as a mosaic (Pfeiffer et al 1992, Rauch et al 1996.…”
Section: Discussionmentioning
confidence: 99%